An Electrochemical Approach for Ultrasensitive Detection of Zearalenone in Commodity Using Disposable Screen-Printed Electrode Coated with MXene/Chitosan Film - Siva Sangu, S. (Springer, 2022)
Zearalenone is a mycotoxin contaminating nearly 56 of agricultural crops globally causing severe health, environmental, and economic effect. This study combines MXene and biodegradable polymer, chitosan (MXene/Chitosan) to develop a highly sensitive thin layer on screen-printed electrode for an effective detection of zearalenone. Successful aluminum etching causes intercalated layers of MXene which provides large surface area for immobilization of biomolecules. Further characterizations verify enhanced electroconductivity, high crystallinity, and presence of biocompatible chemical composition which improves its biosensing application. The MXene/Chitosan aptasensor has limit of detection of 0.4Â pgÂ mlâ1 and shows a good detection of zearalenone in spiked commodity. Graphical abstract: Figure not available: see fulltext. Â© 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.